СОЗДАНИЕ ГЕОИНФОРМАЦИОННОЙ СИСТЕМЫ ДЛЯ РЕШЕНИЯ ЗАДАЧ ПРИРОДОПОЛЬЗОВАНИЯ - Финкельштейн М.Я.; Деев К.В. (My University, 2006)
Presented are requirements to a geoinformation system designed for solution of nature-use problems. Substantiated is the necessity for creating such systems. Presented are results achieved in VNIIgeosystem and future problems to be solved are discussed.
Keywords: 55:025.4.03